Finite Element Analysis of Glass Fiber Reinforced Plastic Concrete Beam Strengthened with Polymer Plate - Fauzi, Mardiana Izyan; Salleh, Norhafizah (Recent Trends in Civil Engineering and Built Environment, 2023)
The uses of the steel reinforced concrete beam in the construction are popular. However, the major problem of using the conventional beam structure is due to the corrosion that tends to produce a damaged structure effected by the cracking and leads in reducing the service life of the structure. GFRP bar was chosen to replace the steel reinforcement in concrete structures because of its superior corrosion resistance, high tensile strength, lightweight, low thermal conductivity, and high specific strength. Unfortunately, GFRP bar produced a larger deflection and cracking due to the low modulus of elasticity. To overcome this problem, strengthening materials has been used to improve the ductility, flexural, and shear capacity of the structural elements. In this study, four types of different fiber polymer plates such as carbon, aramid, glass, and kenaf are used to investigate the flexural behaviour of the beam structure and to determine the type of failure occurred. Each type of material investigated by placing the polymer plates under the beam with different length ratio and different weight to determine the ultimate load for each beam. The study conducted by using ATENA Software and the result has been validated with the experimental data. The result obtained showed that the CFRP plate with the longest span is acceptable to be used as the strengthening object to minimize the deflection of the GFRP concrete beam structure.